Teacher identity and language ideology in english language teaching: a sociolinguistic study from Indonesia - Lailatul Janna (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The global expansion of English has reshaped educational hierarchies and professional identities, particularly in large multilingual contexts such as Indonesia where English functions simultaneously as communicative resource and symbolic capital. Objective: This study aims to investigate how teacher identity and language ideology are constructed, negotiated, and enacted within Indonesian English Language Teaching across institutional and policy contexts. Method: Employing a qualitative multi-sited design, this research integrates language ideology analysis, Positioning Theory, and Critical Discourse Analysis to examine interviews, classroom interactions, professional documents, and national curriculum texts. Results: The findings reveal the coexistence of native-speakerist legitimacy, intelligibility-oriented pragmatism, and localized pedagogical authority within teachers’ discursive repertoires. Identity positions shift dynamically according to institutional pressures, audience design, and testing regimes. Power circulates vertically from macro-policy discourses to micro-classroom practices, producing both stratification and sites of pedagogical resistance. Implication: These findings suggest that teacher identity in Indonesian ELT is dynamically shaped by competing language ideologies and institutional pressures, requiring more context-sensitive policies that recognize localized authority and support equitable professional positioning. Novelty: The novelty of this study lies in its integrated multi-layer analytical model that bridges ideology, positioning, and institutional power, offering a comprehensive framework for examining teacher identity in Global South ELT contexts.